Microscopic, biochemical and physiological aspects of the maize- Stenocarpella macrospora interaction - Bermúdez Cardona, Maria Bianney (2014)
Macrospora leaf spot (MSL), caused by Stenocarpella macrospora, is an important disease of maize. The general objective of this work was investigated some aspects of maize-S. macrospora interaction at microscopic, physiological and biochemical level. In this first study were determined the events of the infection process of S. macrospora in leaves of plants from cultivar HIB 32R48H highly susceptible to S. macrospora. Germinated conidia did not showed positive tropism to stomata. After 24 hai, the germ tubes growth was followed by appressoria formation and the penetration of the germ tubes through the leaf cuticle was mainly direct. After penetration, fungal hyphae first colonized adjacent epidermal cells. At 20 dai, prominent fungal growth was observed in phloem vessels, in the parenchyma cells, in the xylem vessels and bundle sheath cells as well as in the vessel elements. Fungal hyphae emerged through the stomata and pycnidia in different developmental stages were observed in the necrotic leaf tissues at 20 dai. In this second study was investigated the effect of MLS on the photosynthetic performance through the photosynthetic gas exchange parameters and chlorophyll a fluorescence parameter in leaves of plants from two maize cultivars (ECVSCS155 and HIB 32R48H) susceptible and highly susceptible, respectively, to S. macrospora. MLS severity was significantly lower in the leaves of plants from cultivar ECVSCS155 relative to the leaves of plants from cultivar HIB 32R48H. In both cultivars, A, g s and E significantly decreased, while C i /C a increased in inoculated plants relative to non- inoculated plants. F 0 and NPQ significantly increased in inoculated plants of the ECVSCS155 and HIB 32R48H cultivars, respectively, relative to non-inoculated plants. The F m , F v /F m , q P and ETR significantly decreased in inoculated plants relative to non-inoculated plants. For both cultivars, concentrations of total chlorophyll (Chl) (a + b) and carotenoids and the Chl a/b ratio significantly decreased in inoculated plants relative to non-inoculated plants. In this third study were investigated the biochemical and physiological alterations induced by infection process through the chlorophyll a fluorescence imaging and the activities of some antioxidative enzymes and the concentration of ROS in leaves of plants from two maize cultivars (ECVSCS155 and HIB 32R48H) susceptible and highly susceptible, respectively, to S. macrospora. Regardless of maize cultivar, the first changes were observed at 48 hai for all parameters of chlorophyll a fluorescence which prominently increased as the MLS progressed. Decreases in F m , F v /F m , Y(II) and Y(NPQ) coupled with increases in F 0 and Y(NO were directly related to the progressive loss of photosynthetic activity. In both cultivars the enzymatic and non- enzymatic components of the antioxidative system were both dramatically altered on infected leaves. The SOD, CAT, POX, APX, GR, GPX and GST activities as well as the concentrations of AsA and GSH+GSSG were quite higher at the early stages of fungal infection, but suffered accentuated decreases as the MLS progressed suggesting the occurrence of an initial mechanism defense from the host’s side. As the symptoms of MLS on maize leaves become more drastic, the activities of these enzymes, and the concentration of metabolites buffers decreased. Although, H 2 O 2 and MDA concentration increased contributing, therefore, for the intensification of lipid peroxidation upon damage to cell membranes.